2022
DOI: 10.1016/j.meegid.2022.105227
|View full text |Cite
|
Sign up to set email alerts
|

Allele С (rs5186) of at1r is associated with the severity of COVID-19 in the Ukrainian population

Abstract: Introduction The severity of SARS-CoV-2 induced coronavirus disease 19 (COVID-19) depends on the presence of risk factors and the hosts' gene variability. There are preliminary results that gene polymorphisms of the renin-angiotensin system can influence the susceptibility to and mortality from COVID-19. Angiotensin II type 1 receptor (AT1R) might be a gene candidate that exerts such influence. The aim of this study was to elaborate on the association between A1166C at1r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 43 publications
(44 reference statements)
0
13
0
1
Order By: Relevance
“…As RAAS activity is an important regulator of eNOS activity, genetic polymorphisms for molecules in the RAAS signaling axis (Table 2 ) are likely to have significant impact on NO generation, NLRP3 regulation, and endothelial inflammation during MIS-C (Fig. 2 ) [ 15 , 21 , 56 62 , 103 , 104 ]. Polymorphisms of the ACE gene explain 20–50% of the variability in ACE levels and up to 15% of hypertensive cases [ 105 ].…”
Section: The No Genetic Pathway To Mis-cmentioning
confidence: 99%
See 1 more Smart Citation
“…As RAAS activity is an important regulator of eNOS activity, genetic polymorphisms for molecules in the RAAS signaling axis (Table 2 ) are likely to have significant impact on NO generation, NLRP3 regulation, and endothelial inflammation during MIS-C (Fig. 2 ) [ 15 , 21 , 56 62 , 103 , 104 ]. Polymorphisms of the ACE gene explain 20–50% of the variability in ACE levels and up to 15% of hypertensive cases [ 105 ].…”
Section: The No Genetic Pathway To Mis-cmentioning
confidence: 99%
“…Given the fundamental role of RAAS in cardiovascular homeostasis and SARS-CoV-2, RAAS molecule polymorphisms could significantly modulate Ang II activity and increase the risk of a RAAS-induced hyperinflammation with excessive NLRP3 inflammasome activation, when increasing age and co-inherited eNOS activity-reducing NOS3 haplotypes, attenuate EPO effects (Fig. 1 , 2 ) [ 15 , 21 , 22 , 30 , 56 62 , 104 , 106 110 ].…”
Section: The No Genetic Pathway To Mis-cmentioning
confidence: 99%
“…More than 700 mutations, that can overactivate or inactivate the receptors, have been identified and linked to more than 30 distinct human illnesses [ 15 ]. Minor information about AT1R polymorphisms in SARS-CoV-2 patients is found, despite their importance as risk factors in COVID-19 such as those implicated in diabetes, hypertension, and cardiovascular diseases (CVDs) [ 28 ].…”
Section: Angiotensin II Type I Receptor (At1r) and Covid-19mentioning
confidence: 99%
“…The study of Izmailova et al on the Ukrainian population showed an association between COVID-19 severity and the A1166C polymorphism. When compared with A-allele carriers, C allele carriers had significant COVID-19 pathogenicity, as well as higher oxygen requirement due to cardiovascular problems [ 28 ]. In fact, the C allele has been shown to be associated with many CVDs such as systolic blood pressure, left ventricular hypertrophy, hypertension, aortic stiffness, myocardial infarction, carotid intimal–medial thickening, coronary artery disease, and stroke [ 32 , 33 ].…”
Section: Angiotensin II Type I Receptor (At1r) and Covid-19mentioning
confidence: 99%
“…Prolyl hydroxylase domain protein 2 (EGLN1) and HIF-1α inhibitory factor (HIF1AN) are also associated with the pathophysiology of HAPE [8], and abnormally elevated levels of HIF-1α are considered to be a HAPE susceptibility marker [9]. Additionally, angiotensin II type 1 receptor (AT1R) gene polymorphisms might be associated with HAPE susceptibility [10], and A1166C AT1R polymorphism is also associated with COVID-19 severity [11]. Interestingly, a slightly elevated plasma concentration of B-type natriuretic peptide might be related to an exaggerated pulmonary vascular response in hypoxia-susceptible individuals [12], as well as poor outcomes in COVID-19 patients [13].…”
mentioning
confidence: 99%